Nutrition Situation and its Food Policy Links - Kumar, Shubh K. (International Food Policy Research Institute, 1987)
Malnutrition is generally not perceived to be a pervasive problem in much of Africa, except during famines. There is little doubt that in "average" years, malnutrition in Africa is a smaller problem than it is in Asian countries such as Bangladesh, India, Nepal, or Sri Lanka. Another reason why nutritional problems do not receive much attention in Africa is that in recent years episodes of severe drought, famine, and starvation have been relatively frequent, and attention has focused more on the shorter-run alleviation of food problems than on longer-term underlying problems. Finally, the proportion of the undernourished has been almost uniformly lower in urban centers than in rural areas due to a variety of income subsidies, better health, water supply, and sanitation facilities. Because of dispersed habitations and less variation in living standards, the rural problem is seldom visible except when reports of severe famine surface